(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
This study was undertaken to apply Toxoplasma gondii specific IgG avidity test in seropositive pregnant women to differentiate acute and past infection. T. gondii specific IgG avidity test was conducted in 39 seropositive pregnant women and their pregnancy outcomes were observed later on. Out of 39 T. gondii seropositive pregnant women 33 (84%) were only IgG positive and 6 (15.4%) were both IgG-IgM positive. All the IgG positive cases (100%) and 2(33.3%) IgG-IgM positive cases had high avidity antibodies and they gave birth to healthy babies. Rest of the 4 (66.7%) IgG-IgM positive women had low avidity and 50% of them had abortion and 50% gave birth to unhealthy babies. This reveals that the seropositive mothers having high IgG avidity had past infection and no risk of congenital transmission. Seropositive mothers having low IgG avidity had acute infection and so congenital transmission occurred. Presence of T. gondii specific IgG and IgM antibody does not indicate acute infection always. IgG-IgM positive pregnant women should be further evaluated by IgG avidity assay to confirm acute infection.